GSDME-mediated pyroptosis promotes inflammation and fibrosis in obstructive nephropathy - Li, Yinshuang; Yuan, Ying; Huang, Zhong-xing; Chen, Hui; Lan, Ruilong; Wang, Zeng; Lai, Kunmei; Chen, Hong; Chen, Zhimin; Zou, Zhenhuan; Ma, Hua-bin; Lan, Hui-Yao; et al. (Cell death and differentiation, 2021)
Renal tubular cell (RTC) death and inflammation contribute to the progression of obstructive nephropathy, but its underlying mechanisms have not been fully elucidated. Here, we showed that Gasdermin E (GSDME) expression level and GSDME-N domain generation determined the RTC fate response to TNFα under the condition of oxygen-glucose-serum deprivation. Deletion of Caspase-3 (Casp3) or Gsdme alleviated renal tubule damage and inflammation and finally prevented the development of hydronephrosis and kidney fibrosis after ureteral obstruction. Using bone marrow transplantation and cell type-specific Casp3 knockout mice, we demonstrated that Casp3/GSDME-mediated pyroptosis in renal parenchymal cells, but not in hematopoietic cells, played predominant roles in this process. We further showed that HMGB1 released from pyroptotic RTCs amplified inflammatory responses, which critically contributed to renal fibrogenesis. Specific deletion of Hmgb1 in RTCs alleviated caspase11 and IL-1β activation in macrophages. Collectively, our results uncovered that TNFα/Casp3/GSDME-mediated pyroptosis is responsible for the initiation of ureteral obstruction-induced renal tubule injury, which subsequentially contributes to the late-stage progression of hydronephrosis, inflammation, and fibrosis. This novel mechanism will provide valuable therapeutic insights for the treatment of obstructive nephropathy.